2020
DOI: 10.3390/antiox10010032
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Antidesma bunius Fruit Extract on Carbohydrate Digestive Enzymes Activity and Protein Glycation In Vitro

Abstract: Antidesma bunius (L.) spreng (Mamao) is widely distributed in Northeastern Thailand. Antidesma bunius has been reported to contain anthocyanins, which possess antioxidant and antihypertensive actions. However, the antidiabetic and antiglycation activity of Antidesma bunius fruit extract has not yet been reported. In this study, we investigated the inhibitory activity of anthocyanin-enriched fraction of Antidesma bunius fruit extract (ABE) against pancreatic α-amylase, intestinal α-glucosidase (maltase and sucr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 65 publications
1
11
0
Order By: Relevance
“…The A. bunius fruit fraction showed the highest free radical scavenging activity through the DPPH test of 97.39 ± 2.48% compared to other organs (Quiming et al, 2016). The antioxidant power of A. bunius leaf FRAP has IC50 182.22 0.64 g/mL (Aksornchu et al, 2021). A similar was reported by Islary et al (2017) which stated that A. bunius fruit had a FRAP antioxidant value of 61.583±3.818 M TE/g DE.…”
supporting
confidence: 68%
See 2 more Smart Citations
“…The A. bunius fruit fraction showed the highest free radical scavenging activity through the DPPH test of 97.39 ± 2.48% compared to other organs (Quiming et al, 2016). The antioxidant power of A. bunius leaf FRAP has IC50 182.22 0.64 g/mL (Aksornchu et al, 2021). A similar was reported by Islary et al (2017) which stated that A. bunius fruit had a FRAP antioxidant value of 61.583±3.818 M TE/g DE.…”
supporting
confidence: 68%
“…Antidesma bunius has activity as antibacterial, anti-inflammatory (Pongnaratorn et al, 2017), anti-oxidant, anti-hypertensive (Aksornchu et al, 2021), anti-microbial (Yelliantty et al, 2021), and anticancer (Pongnaratorn et al, 2017;Yelliantty et al, 2021). The bioactivity of A. bunius is related to its secondary metabolite content such as anthocyanins (Aksornchu et al, 2021), 5hydroxymethylfurfural (HMF), furaldehyde, and citric acid (Yelliantty et al, 2021). Anthocyanins have activity as antioxidants and anti-hypertensives (Aksornchu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, inhibition of AGE formation is another approach in delaying or preventing the onset of diabetic complications [ 48 ]. Many studies conducted on fruits indicated that phenolic compounds were the functional components that played a major role in their hypoglycemic effect [ 7 , 8 , 9 , 12 , 27 , 31 , 49 , 50 , 51 , 52 ]. Thus, in order to verify this hypothesis in our research, the V. opulus fruit samples varying in terms of degree of purification of phenolic compounds and thus in the presence of other non-phenolic components were used.…”
Section: Discussionmentioning
confidence: 99%
“…Other relationships were found in the BSA-fructose measurement system, where only crude extract (CE) of V. opulus fruit was a weaker inhibitor of AGE formation compared to aminoguanidine. The higher IC 50 values obtained with BSA-glucose compared to BSA-fructose are probably due to higher reactivity of ketose sugar than which has a more open-chain structure than aldose sugar [ 51 ]. Regardless of the test used, the ethyl acetate fraction (PEAF) showed the strongest inhibitory properties against the formation of fluorescent AGE.…”
Section: Discussionmentioning
confidence: 99%